Point Absorber Method as Wave Energy Convertor Device for Power Generation: Effect of Buoy Arrangements - Yussof, M. A.; Ismail, N. I.; Aiman, M. J.; Abdullah, M. F.; Gurunathan, B. A.; A. Rahman, M. R.; Saad, M. R. (International Journal of Integrated Engineering, 2020)
A point absorber is a floating structure with components that move relative to each other due to wave action. They utilize the up and down movement of the wave height at a single point for energy conversion. The relative up and down which is bobbing motion caused by passing waves used to drive electromechanical energy converters to generate power output. This experiment investigates behaviour of the point absorber device used the pneumatic sensor to take the frequency of the displacement of buoy while testing in the wave maker generator. Then, study the efficiency power output of point absorber WEC device and studies the behaviour of the point absorber in a regular wave. Fabricate the linear generator which as power absorption to estimate the effectiveness power output on different configuration by using the multimeter device. The point absorber at the front position of the configuration has good behaviour because of the high frequency produced. By estimated the behaviour of the device on configuration achieved. Configuration shape design of the point absorber used in this testing is square, diamond and parallelogram shape for an estimate the best power output. The configuration of the parallelogram has the best power output compared to another configuration. The best arrangement of the device for efficiency by measure the output voltage as power output is 68.14 mV and increase 8% in every minute.